2013
DOI: 10.1371/journal.pgen.1003910
|View full text |Cite
|
Sign up to set email alerts
|

Survival of the Replication Checkpoint Deficient Cells Requires MUS81-RAD52 Function

Abstract: In checkpoint-deficient cells, DNA double-strand breaks (DSBs) are produced during replication by the structure-specific endonuclease MUS81. The mechanism underlying MUS81-dependent cleavage, and the effect on chromosome integrity and viability of checkpoint deficient cells is only partly understood, especially in human cells. Here, we show that MUS81-induced DSBs are specifically triggered by CHK1 inhibition in a manner that is unrelated to the loss of RAD51, and does not involve formation of a RAD51 substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
124
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(134 citation statements)
references
References 66 publications
9
124
1
Order By: Relevance
“…Several lines of evidence support the hypothesis that Chk1 avoids the collapse of ongoing forks: i) Chk1 pharmacological inhibition or depletion by siRNA lead to increased accumulation of replication-associated DSBs (Forment et al, 2011; Murfuni et al, 2013; Sorensen et al, 2005; Syljuasen et al, 2005); ii) CHOC cells treated with the Chk1 inhibitor UCN-01 and Chk1−/− avian B-lymphoma cells show reduced ability to resume replication after an APH-induced arrest (Feijoo et al, 2001; Zachos et al, 2003); iii) Chk1 inactivation reduces the rate of replication fork progression in unperturbed, UV-exposed and CPT-treated cells (Petermann and Caldecott, 2006; Seiler et al, 2007; Speroni et al, 2012). Although these results suggest that Chk1 stabilizes replication forks, impaired fork elongation in Chk1-deficient backgrounds may represent an indirect effect of elevated origin firing (Petermann et al, 2010).…”
Section: Chk1 Function During Dna Replicationmentioning
confidence: 88%
See 2 more Smart Citations
“…Several lines of evidence support the hypothesis that Chk1 avoids the collapse of ongoing forks: i) Chk1 pharmacological inhibition or depletion by siRNA lead to increased accumulation of replication-associated DSBs (Forment et al, 2011; Murfuni et al, 2013; Sorensen et al, 2005; Syljuasen et al, 2005); ii) CHOC cells treated with the Chk1 inhibitor UCN-01 and Chk1−/− avian B-lymphoma cells show reduced ability to resume replication after an APH-induced arrest (Feijoo et al, 2001; Zachos et al, 2003); iii) Chk1 inactivation reduces the rate of replication fork progression in unperturbed, UV-exposed and CPT-treated cells (Petermann and Caldecott, 2006; Seiler et al, 2007; Speroni et al, 2012). Although these results suggest that Chk1 stabilizes replication forks, impaired fork elongation in Chk1-deficient backgrounds may represent an indirect effect of elevated origin firing (Petermann et al, 2010).…”
Section: Chk1 Function During Dna Replicationmentioning
confidence: 88%
“…Particularly, Chk1 phosphorylates Rad51 and BRCA2 to stimulate the recruitment of Rad51 to sites of DNA damage (Bahassi et al, 2008; Sorensen et al, 2005). Nuclease-mediated accumulation of DSBs after Chk1 inhibition or depletion reveals that, apart from promoting HR-dependent processing of DSBs, Chk1 prevents the accumulation of DSBs in the first place (Forment et al, 2011; Murfuni et al, 2013; Syljuasen et al, 2005). Specifically, DSB formation in Chk1-deficient cells is catalyzed by the Mus81 endonuclease (Forment et al, 2011; Murfuni et al, 2013) and the MRE11 nuclease (Thompson et al, 2012).…”
Section: Chk1 Function During Dna Replicationmentioning
confidence: 99%
See 1 more Smart Citation
“…A role for Rad52 in BIR can explain why its depletion in cells with DRS leads to increased DNA damage (Wray et al., 2008, Murfuni et al., 2013, Galanos et al., 2016; Figures 3A and 3B), why the RAD52 gene is amplified in human cancers, and why its inactivation curtails cancer development (Treuner et al., 2004, Cramer-Morales et al., 2013, Lieberman et al., 2016; Figure 4). BIR also mediates DNA repair synthesis in mitosis (Minocherhomji et al., 2015), and it is noteworthy that Rad52 is essential also in this context (Bhowmick et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These findings have indicated that MUS81 plays a key role in the maintenance of genetic stability. Meanwhile, some works demonstrated that MUS81 interacts with checkpoint proteins, such as Checkpoint kinase 1 [12] and Checkpoint kinase 2 [13], suggesting the association between MUS81 and cell cycle progression.…”
Section: Introductionmentioning
confidence: 99%